22 Del. Laws 403 (1901) - (:unkn) unknown (My University, 1901)
The Commissioners may also pass ordinances to . . . regulate the storage of gunpowder or any other dangerous or combustible materials . . .§.
Keywords: GUNPOWDER - STORAGE